A remote patient monitoring based on WBAN implementation with internet of thing and cloud server - Jaber H. Majeed; Qais Aish (Bulletin of Electrical Engineering and Informatics, 2021)
A healthcare employment is the mainly domain in emergent technology of WBAN, and an e-health system created of cloud computing in addition to a WSN considers an important part of this field. An implementation of remotely system for monitoring the patient's vital signs require continuous observation to form low-cost networks with the ability of portability and flexibility and may be applied with separate position and long-term intensive care of peoples in the absence of disturbance of their everyday activities. The patient carries body sensor's patches to get transmitted vital signs continuously to the cloud environment, and a website is designed for presenting and analyzing the data based on designed algorithm. A comparison is made every received measurement with a that stored in the algorithm. In remote specialist care, the execution of confidence and confidentiality conservation is critical, as essential restrictions were being communicating with remote locations. To ensure reliability, the implemented system offers real time monitoring and certification to the patient's condition by means of a medical record, with rapid medical data delivery to the medical staff and can also increase the service delivery ratio of hospital capacity and monitoring of large number of patients with concentrated average delay.